PENYUSUNAN ANGGARAN KOMPREHENSIF SEBAGAI ALAT PERENCANAAN DAN PENGENDALIAN LABA PADA PT SHINDO TIARA TUNGGAL - Aryanto Aryanto; Fikky Sherlinadya; Neng Ima Rahmayanti; Rachmat Agus Santoso (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2023)
This research was conducted at PT. Shindo Tiara Tunggal is a company engaged in thesnack food industry. The purpose of conducting this research is to find out and analyze thepreparation of the sales budget as a means of planning and controlling profits.The data usedwill be analyzed using qualitative methods, namely this research begins with data collection,observation and analysis of documents related to the object of research and ends with drawingconclusions. The data collection technique used is by interviewing and observing the company'sactivities.Based on the research conducted at the company, a problem was found, namely that itcould be seen that the control carried out by PT. Shindo Tiara Tunggal related to theoperational activity of selling snacks is not optimal, this is because the company does not yethave work standards or work targets which are manifested in the form of plans to prepare asales budget and costs related to operational sales of the company's products.